1998
DOI: 10.1143/jjap.37.l1195
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dislocation in InGaN Phase Separation

Abstract: The role of dislocation for luminescence in InGaN grown on sapphire substrate by metal organic chemical vapor deposition (MOCVD) method was investigated by cathodoluminescence (CL) and atomic force microscopy (AFM). The CL emission area and dark spots between InGaN and GaN layers in InGaN/GaN single quantum well (SQW) and multiple quantum well (MQW) structures showed completely one to one correspondence. These results indicate that dislocations in InGaN work as non-radiative recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 13 publications
5
78
2
Order By: Relevance
“…The typical dislocation density of a GaN film on FIELO GaN and sapphire substrate was %10 7 and %10 9 cm ± ± 2 , respectively. be seen, as were observed in previous studies [9,10]. The estimated density of pits was about 10 9 cm ± ±2…”
Section: Methodssupporting
confidence: 88%
“…The typical dislocation density of a GaN film on FIELO GaN and sapphire substrate was %10 7 and %10 9 cm ± ± 2 , respectively. be seen, as were observed in previous studies [9,10]. The estimated density of pits was about 10 9 cm ± ±2…”
Section: Methodssupporting
confidence: 88%
“…The spatial inhomogeneity of NSOM-PL is well known and interpreted to be the inhomogeneity of indium composition by the phase separation. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The bright regions correspond to the high density region of the carrier localization centers, which act as the radiative recombination centers ͑RCs͒. On the other hand, the spatial inhomogeneity of NSOM-TL should denote the carrier distribution in the InGaN active layer because we already knew that the NSOM-TL signal is attributed to only the ␦N ͓Fig.…”
Section: ͑1͒mentioning
confidence: 99%
“…1,2 In order to improve the efficiency of light emission from InGaN QW, we have to elucidate and understand the carrier dynamics and light emission mechanics. There are a lot of reports on the spatial resolved studies for InGaN by cathodoluminescence, [3][4][5] near-field scanning optical microscopy ͑NSOM͒, [6][7][8][9][10][11][12] or scanning confocal microscopy. 13,14 By these techniques, the radiative carrier recombination process has been observed with submicrometer scale.…”
mentioning
confidence: 99%
“…Sugahara [3] discussed the role of dislocations in the InGaN phase separation. He showed that dislocations in InGaN act as nonradiative recombination centers and confirmed that the phase separation in InGaN is caused by spiral growth due to mixed dislocations.…”
Section: Introductionmentioning
confidence: 99%